2022
DOI: 10.1177/1759720x211066233
|View full text |Cite
|
Sign up to set email alerts
|

Wearable transcutaneous electrical nerve stimulation (actiTENS®) is effective and safe for the treatment of knee osteoarthritis pain: a randomized controlled trial versus weak opioids

Abstract: Introduction: Despite their poor tolerance, especially in the elderly, weak opioids (WO) remain commonly prescribed for patients with knee osteoarthritis (KOA). We compared the efficacy and safety of a new wearable transcutaneous electrical nerve stimulation (W-TENS) device with WO for the treatment of moderate-to-severe, nociceptive KOA chronic pain. Methods: The study was a non-inferiority, multicentric, prospective, randomized, single-blind, controlled, 2-parallel groups Trial. A total of 110 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the average eight-day pain intensity index, The W-TENS and WO(weak opioids) groups were 3.87 (2.12) and 4.66 (2.37), respectively. Among the treatment-related adverse events, seven patients were reported in the W-TENS group versus 36 patients in the WO group, this shows that W-TENS is obviously better than WO in treating KOA pain [22].…”
Section: Advantagesmentioning
confidence: 88%
“…In the average eight-day pain intensity index, The W-TENS and WO(weak opioids) groups were 3.87 (2.12) and 4.66 (2.37), respectively. Among the treatment-related adverse events, seven patients were reported in the W-TENS group versus 36 patients in the WO group, this shows that W-TENS is obviously better than WO in treating KOA pain [22].…”
Section: Advantagesmentioning
confidence: 88%
“…Quadriceps strengthening exercises using the quadriceps bench will increase the number of sarcomeres and muscle fibers (actin and myosin filaments needed in muscle contraction), causing an increase in muscle strength. If the exercise is performed repeatedly, it will increase stability and reduce subchondral inflammation in the capsule, thereby reducing pain [ 9 , 10 ].…”
Section: Reviewmentioning
confidence: 99%
“…Reproduced with permission. [76] Copyright 2022, the authors. (h) Improvement in OAB symptom scores of placebo and TENS groups.…”
Section: Electrical Neuromodulationmentioning
confidence: 99%
“…Maheu et al conducted a randomized controlled trial on patients with knee osteoarthritis and found that a wearable TENS device, shown in Figure 2g, was effective in reducing chronic pain. [76] Moreover, the authors demonstrated that the non-pharmacological TENS method was more effective and safer than the weak opioids commonly used as pain relievers, an important finding as safety is of significant concern when treating chronic pain. Numerous other studies have investigated the use of TENS for managing neuropathic pain, including in conditions such as diabetic peripheral neuropathic pain and postherpetic neuralgia.…”
Section: Electrical Neuromodulationmentioning
confidence: 99%
See 1 more Smart Citation